Multi-omics uncovers immune-modulatory molecules in plasma contributing to resistance exercise-ameliorated locomotor disability after incomplete spinal cord injury - Ren Zhou; Jibao Chen; Yunhan Tang; Chuijin Wei; Ping Yu; Xinmei Ding; Li’ao Zhu; Jiajia Yao; Zengqiang Ouyang; Jing Qiao; Shumin Xiong; Liaoliao Dong; et al. (Genome Medicine)
Abstract Background Exercise rehabilitation therapy has garnered widespread recognition for its beneficial effects on the restoration of locomotor function in individuals with spinal cord injury (SCI). Notably, resistance exercise has demonstrated significant improvements in muscle strength, coordination, and overall functional recovery. However, to optimize clinical management and mimic exercise-like effects, it is imperative to obtain a comprehensive understanding of the molecular alterations that underlie these positive effects. Methods We conducted a randomized controlled clinical trial investigating the effects of resistance exercise therapy for incomplete SCI. We integrated the analysis of plasma proteomics and peripheral blood mononuclear cells (PBMC) transcriptomics to explore the molecular and cellular changes induced by resistance exercise. Subsequently, we established a weight-loaded ladder-climbing mouse model to mimic the physiological effects of resistance exercise, and we analyzed the plasma proteome and metabolome, as well as the transcriptomes of PBMC and muscle tissue. Lastly, to confirm the transmissibility of the neuroprotective effects induced by resistance exercise, we intravenously injected plasma obtained from exercised male mice into SCI female mice during the non-acute phase. Results Plasma proteomic and PBMC transcriptomic profiling underscored the notable involvement of the complement pathways and humoral immune response in the process of restoring locomotor function following SCI in the human trial. Moreover, it was emphasized that resistance exercise interventions could effectively modulate these pathways. Through employing plasma proteomic profiling and transcriptomic profiling of PBMC and muscle tissues in mice, our study revealed immunomodulatory responses that parallel those observed in human trials. In addition, our analysis of plasma metabolomics revealed an enhancement in lipid metabolism following resistance exercise. We observed that resistance exercise plasma exhibited significant effects in ameliorating locomotor disability after SCI via reducing demyelination and inhibiting neuronal apoptosis. Conclusions Our investigation elucidates the molecular alterations associated with resistance exercise therapy promoting recovery of locomotor function following incomplete SCI. Moreover, we demonstrate the direct neuroprotective effects delivered via exercise plasma injection, which facilitates spinal cord repair. Mechanistically, the comprehensive multi-omics analysis involving both human and mice reveals that the principal constituents responsible for the observed neuroprotective effects within the plasma are predominantly immunoregulatory factors, warranting further experimental validation. Trial registration The study was retrospectively registered on 17 July, 2024, in Chinese Clinical Trial Registry (No.: ChiCTR2400087038) at https://www.chictr.org.cn/ .